1996
DOI: 10.1111/j.1365-2621.1996.323-26.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical, chemical and sensory characteristics of cooked meat emulsion style products containing vegetable oils

Abstract: Beef frankfurters and cooked salamis (containing 19.5% pork back fat) were compared with samples containing vegetable oils. The pork back fat was replaced with Soya‐seed oil (19.5%), sunflower oil (19.5%, 24%, 27.5%), cotton‐seed oil (19.5%), corn‐seed oil (19.5%) or palmine (19.5%). The emulsion stability of the products containing vegetable oil was good, even if the temperature of the batters reached 20°C. However, firmness, lightness of internal colour and flavour intensity were reduced in the vegetable oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 9 publications
(10 reference statements)
7
33
1
1
Order By: Relevance
“…As can be observed in Table 5, a high capacity to hold water and fat exudates was obtained in canola-olive oil emulsions, although TEF was unaffected (P > 0.05) by differences on fat (0.64 AE 0.17) and vegetable oils (w0.61e0.55) formulations. These results are consistent with those obtained by Ambrosiadis et al (1996), which found cooking loss values in batters containing vegetable oils significantly (P < 0.05) lower than batter controls containing pork backfat. The TEF values (Table 5) for emulsions formulated with RB were found to be not significantly (P > 0.05) different compared with emulsions with no extracts, but were significantly (P < 0.05) higher than emulsions with added WE.…”
Section: Rep Fateoils Extractssupporting
confidence: 95%
See 1 more Smart Citation
“…As can be observed in Table 5, a high capacity to hold water and fat exudates was obtained in canola-olive oil emulsions, although TEF was unaffected (P > 0.05) by differences on fat (0.64 AE 0.17) and vegetable oils (w0.61e0.55) formulations. These results are consistent with those obtained by Ambrosiadis et al (1996), which found cooking loss values in batters containing vegetable oils significantly (P < 0.05) lower than batter controls containing pork backfat. The TEF values (Table 5) for emulsions formulated with RB were found to be not significantly (P > 0.05) different compared with emulsions with no extracts, but were significantly (P < 0.05) higher than emulsions with added WE.…”
Section: Rep Fateoils Extractssupporting
confidence: 95%
“…As a result, pork backfat emulsions showed significantly (P < 0.05) lower energy values than other frankfurters made with vegetable oils or extracts (RB and WE). Similarly, other authors found reduced values of fat content in beef frankfurters and cooked salamis in comparison with samples containing vegetable oils (Ambrosiadis, Vareltzis, & Georgakis, 1996), as well as decreases of energy values (27e38%) in frankfurters with reduced-fat compositions (Cengiz & Gokoglu, 2005). The addition of rice bran and walnut paste significantly (P < 0.05) raised the ash (rice bran) and fat (walnut paste) contents of frankfurters (Table 4).…”
Section: Proximate Analysis and Energy Values Of Frankfurtersmentioning
confidence: 79%
“…However, the link of fat with cardiovascular disease has led to change in commercial meat product formulations in favor of reduced fat or substitution of fat with vegetable oils. Ambrosiadis et al (1996) experimented with replacing animal fat (20% of product weight) in beef frankfurters by vegetable oils (soy, sunflower, cotton, corn, or palmine) and reported acceptable sensory properties. Bloukas et al (1997) also reported that up to 20% of pork backfat could be replaced by olive oil in the form of an emulsion without negatively affecting the processing and quality characteristics of dry fermented sausages.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their physicochemical characteristics oil-in-water emulsions (pre-emulsions) are a suitable technological option for stabilizing the non-meat fats added to meat derivatives as ingredients (Bishop, Olson & Knipe, 1993;Djordjevic, McClements & Decker, 2004). There are a number of procedures that can be used to produce a plant or marine oil-in-water emulsion (with an emulsifier, typically a protein of non-meat origin) for incorporation in meat derivatives (Jiménez-Colmenero, 2007), but only sodium caseinate has been used to stabilize olive oil for incorporation in frankfurter-type products (Paneras & Bloukas, 1994;Ambrosiadis, Vareltzis & Georgakis, 1996;Paneras et al, 1998;Pappa et al, 2000;Choi et al, 2009). As far as the authors are aware, there are no references in the literature to studies on the influence of emulsified olive oil stabilizing systems used as animal fat replacers in frankfurters.…”
Section: Introductionmentioning
confidence: 99%